The Effect of Credit Distribution and Interest Rates on Profitability at Bank Sulselbar Jeneponto Branch - Wairooy, Mohamad Ali; Rahmi, Rahmi (Perpustakaan dan Penerbitan Unismuh Makassar, 2022)
The research is airned to find out that have the Credit distribution and the interest rate influence to Bank Sulselbar at Jeneponto. The data collecting used the secondary data and the population is the bank financial statements including balance sheet and profit and loss statement from 2017 until 2019. The sample of loss statements from banking sector within 3 years of period. Hypothesis testing used linear regression tehnique analysis by SPSS 24 version. The result of the research showed that the influence of credit distribution and the interest rate have no influence to the Bank Sulselbar at Jeneponto.